The Negotiation of Identities Through Humorous Discourse in Political Resistance: An Analysis of Bassem Youssef's 'The B+ Show' - Aref, Howaida (AUC Knowledge Fountain, 2025)
This study examines the strategic use of humorous discourse in negotiating identities and expressing political resistance during the 2011 Egyptian Revolution, focusing on Bassem Youssef's satirical YouTube show, "The B+ Show." Employing a mixed-method approach that combines Grice's maxims of cooperative communication and Fairclough's critical discourse analysis framework, the research investigates how humor functioned as a tool for challenging hegemonic narratives and power dynamics through constructing and deconstructing identities in a volatile sociopolitical context. The analysis reveals that Youssef skillfully exploited various discursive resources, particularly intertextuality and the flouting of conversational maxims, to generate implicatures that effectively debunked negative representations of protesters propagated by state-controlled media. Through irony, sarcasm, and mockery, Youssef's humor served to deconstruct the credibility of anti protest figures while simultaneously constructing positive identities for the protesters. The study is important for stakeholders in foreign language teaching because it highlights the importance of examining a humorous discourse's pragmatic, discursive, and contextual dimensions to incorporate it in foreign language classes.